Financial constraints on firm growth: the role of firm age in the ASEAN–6 - Ling Ng, Yee; Theng Lau, Wei; Ni Soh, Wei; Ab Razak, Nazrul Hisyam (Liverpool University Press, 2024)
The paper assesses the moderating role of firm age in the relationship between financial constraints, as measured by the KZ index, and the WW index on three alternative measures of firm growth (Asset growth, ROA, and ROE) in the ASEAN–6 region. This study employs a sample of ASEAN–6 listed firms over the period 2009–2019 using Fixed Effects and the System GMM model. Firm age is found to interact positively with financial constraints in their effects on firm growth. The negative impact of financial constraints on firm growth is less severe with older age firms.